Analysis of the Impact of Leadership Style and Perceived Organizational Support on Employee Performance Mediated with Work Motivation Case Study Account Officer Micro ULaMM PNM Madiun Branch - Arianto, Rony Dwi; Jahja, Adi Susilo (Jurnal Multidisiplin Madani, 2024)
This research aims to analyze the influence of leadership style and perceived organizational support (POS) on employee performance with work motivation as an intervening variable. Data collection methods were carried out using questionnaires and interviews. The population that was the object of research was the entire ULaMM AOM with a sample of 71 people. This research uses partial least squares (PLS) to test the hypothesis. The results of this research show that leadership style and POS have a positive effect on employee performance. Leadership style does not affect motivation, but POS affects motivation. Motivation also does not affect performance. In addition, work motivation cannot mediate the relation between leadership style and POS on employee performance